Upaya Penumbuhan Karakter Profil Pelajar Pancasila Melalui Uji Boraks Pada Materi IPA Zat Aditif - Kusumaningsih Kusumaningsih (WASIS : Jurnal Ilmiah Pendidikan, 2022)
The purpose of this research is to cultivate the character of the Pancasila Student Profile who is able to collaborate, reason critically and creatively through practicum activities testing borax various food ingredients on science material additives class VIII SMP 3 Satu Atap Undaan.This research is a quantitative research with a quasi-experimental research type. The design in this study used the one group posttest only design. The research subjects were 17 students of class VIII SMP 3 Satu Atap Undaan. The data collection technique was carried out using observation techniques. The instrument used is in the form of student observation sheets. The data obtained were then analyzed in a quantitative descriptive manner with percentagesThe results showed that the implementation of the borax test practicum learning, can foster the character of the Pancasila Student Profile (Collaboration, Critical Reasoning, and Creative) in students. The percentage of collaboration character growth of 100% is in the highly developed criteria. Critical reasoning characters with highly developed criteria are at a percentage of 35.3% and 64.7% in developing criteria. Creative character is shown by the percentage of 29.4% in very developed criteria, 23.5% in developing criteria and 47.1% in developing criteria.